Gerenciamento de resíduos industriais : uma avaliação de desempenho ambiental aplicado nas indústrias metal-mecânica em um município de médio porte - Barbacovi, Naira Elizabete (2013)
The increasing of the industrialization brings environmental problems, one of them is the waste generated by the industries in their processes. In this sense, the concern of preserving the environment through the minimizing the generation of waste is fundamental. In this perspective, the proper management of industrial solid waste is an important factor for expanding economic infrastructure, social and environmental situation. The city of Erechim, located in the Rio Grande do Sul state, had a strong growth in its economy recently, with emphasis on the metal mechanic industries sector. Thus, the study has as the purpose of to conduct a performance evaluation of the environmental management system of the Metal-mechanical industries in Erechim, RS in respect of waste generated by these industries. The methodology is characterized as a survey, and the researches of this type are constituted by direct interrogation of people whose behavior is desired to know. To obtain the information it was held field visits and application of a semi-structured questionnaire. As a result, we obtained an approximate number of 80 metal-mechanical industries existing in the municipality of Erechim, RS, which 30 % agreed to participate in the study, representing 25 area of expertise and businesses. Regarding the forms of waste management, it was found that the industries do not have a specific form of management, however, all companies make the separation, identification and storage according the standards in relation to final disposal. Almost the totality of waste are sent to companies licensed to do the final disposition. Regarding environmental performance indicators, it was found that the industries adopt certain environmental practices, and the main practice it is related with the awareness of employees in relation to the environment. In general it was found that the industries are conscious about the environment, and the only indicator that was not found was the waste management